Perlindungan Hukum Pemegang Saham Publik Akibat Dilusi Kepemilikan Saham Pasca Pelaksanaan Penambahan Modal Tanpa Hak Memesan Efek Terlebih Dahulu - Chen, Zefanya Angellin; Adam, Richard C. (Legal Standing : Jurnal Ilmu Hukum, 2025)
Capital Increase Without Preemptive Rights (PMTHMETD) is a measure taken by the Company to increase capital without offering new shares to existing shareholders in order to implement a settlement plan. Legally, PMTHMETD is regulated in the 2007 Company Law and POJK 14./2019. However, the implementation of PMTMETD results in share dilution for shareholders, especially for public shareholders who are not involved in the voting process. This mechanism often causes dilution of share ownership, especially for public shares owned by the public, who have relatively lower voting rights compared to Majority Shareholders, and especially in the General Meeting of Shareholders (GMS) as a form of approval of the settlement plan. The 2007 UUPT and POJK 14./2019 regulate the mechanism for issuing new shares, but these provisions do not provide substantive protection for public shareholders because public shareholders are in a position to accept without being given the right to make decisions, while majority/controlling shareholders are involved in the decision-making process to approve the settlement plan and are aware of the risks of share ownership dilution. As a result, public shareholders are often in a passive position, accepting policies without the right to make decisions. This study aims to analyze the form of legal protection for public shareholders whose shares are diluted after the implementation of capital increases without preemptive rights. Considering that the settlement plan is a legal product, public shareholders are in a dilemma of not accepting the Company's actions. The type of research used is normative juridical with a literature study using primary, secondary, and tertiary materials and qualitative data. The results of the study will describe the obstacles and forms of legal protection for public shareholders to obtain equality and legal protection.